Activity and Formation of Sand Waves on Northern South China Sea Shelf - 栾锡武 彭学超 王英民 邱燕 (Journal of earth science (Wuhan, China), 2010)
Sand waves on the northern South China Sea shelf had been considered as stable relict bed form. For the industry use of sea bed between stations LF13-2 and LF13-1, a new round of explorations were conducted. The newly obtained data show that both spacings and amplitudes of sand waves are all systematically changing with water depth. Repeated observations since 2003 to 2004 showed that the sea bed is currently active. Due to strong erosion of surface sediment since Dongsha （东沙） uplifting, there are almost no modern sediments on the shelf of Dongsha area. Sand materials in the study area mainly originate from the erosion of the bed sediment formation. The water depth increment revealed by repeated echo sounder data is mainly due to erosion. Bottom currents are quite complex in the area of Dongsha underwater plateaus. At site 9MKH, the southward ebb current is stronger than the north- ward flood current, while at site AEM-HR, the WNW-ward flood current is slightly stronger than the ESE-ward ebb current. At site 9MKII, the maximum bottom current speed is 48 cm/s, and 22% of the observed bottom current speeds are larger than 20 cm/s, which meet the minimum bottom current speed required for the creation of sand wave. This article points out that present-day oceanographic condition couples well with the sand-wave morphologies, and that the sand waves are to a great extent in equilibrium with the ongoing present-day oceanographic bottom current condition and active.